A Workload Indicators of Staffing Need (WISN) based framework and implementation tool for dietitians at South African central and tertiary public hospitals - Vertharani Nolene Naicker; Jane W. Muchiri; Keshan Naidoo; Modiehi Heather Legodi (BMC Health Services Research)
Abstract Background Quality nutrition services are dependent upon the accessibility and availability of nutrition professionals. In this study, we used the World Health Organization’s Workload Indicators of Staffing Need (WISN) methodology to develop a dietetic staffing norm framework and implementation tool for South African central and tertiary public hospitals. Methods We followed the eight step WISN methodology as a basis for this developmental study. National data on permanently employed dietitians in public hospitals were used to determine the facility type. Available working time (AWT) was determined using WISN calculations and SA labour regulations. Consensus on workload components (WC) and activity standards (AS) was achieved through a Delphi exercise. Steps 5 to 8 ended in determination of dietitian requirements based on WISN software. Similar steps were used to develop the framework and tool. The tool’s calculated outputs were compared against the WISN software. Results Central and tertiary public hospitals were identified as the target facilities. Dietitians AWT at these facilities was calculated as 1528 h per year. A final list of 45 WC and aligned AS was obtained and provided the necessary contextualization. A WISN based framework, and a Microsoft Excel tool (calculator) resulted. Calculated average dietitians’ requirements were 24.59 and 24.23 for WISN software and the excel tool respectively. Conclusion The WISN methodology is a versatile tool that allows for the development of context and cadre specific staffing norm implementation frameworks and tools. The developed tool is valid and contextualized to determine the specific need for dietitians at SA central and tertiary public hospitals. These results will help policy makers to plan and forecast dietetic staffing needs at a macro level.